Discrepancies in gut microbial communities and serum metabolites of Hu sheep with different backfat thickness - Li, Bo; Xu, Wenwen; Wang, Wenjia; Mao, Mengyuan; Huang, Xiaoyu; Zhang, Enping (Frontiers in Microbiology, 2025)
Although market demand for lean meat continues to rise, the regulatory mechanisms governing backfat thickness (BFT) metabolism remain poorly understood. This study employed a multi-omics approach to investigate BFT-associated differences in Hu sheep with distinct fat deposition phenotypes. From 160 genetically similar Hu sheep, we selected 12 individuals with non-significant weight differences (P > 0.05) but extreme divergence in BFT [6 high-BFT (HBF) and 6 low-BFT (LBF) individuals]. Using integrated metagenomics and metabolomics, we systematically compared ileal microbial community structure and serum metabolic profiles between the two groups. HBF sheep showed significantly increased adiposity and altered ileal microbiota composition, characterized by elevated abundances of Carnobacterium, Parabacteroides distasonis, Lactiplantibacillus, and Bifidobacterium. Serum metabolomics identified key differential glycerophospholipids-1-(9Z-octadecenoyl)-2-(11Z-eicosenoyl)-glycero-3-phosphate, PE-NMe(15:0/20:3(5Z,8Z,11Z)), PE-NMe2(18:1(9Z)/20:0), and PE-NMe2(18:1(9Z)/22:1(13Z))-all enriched in glycerophospholipid metabolism pathways. Integrated correlation analysis revealed strong associations between P. distasonis abundance and these phospholipids. These results demonstrate BFT-related adaptive remodeling of the serum metabolome and gut microbiota, identifying P. distasonis as a potential modulator of the host-microbe metabolic axis in ovine adiposity regulation.